Natural lighting strategies in the design of affordable housing: the Mihouse case, Solar Decathlon 2015 (2019)
In the design of low cost housing without air conditioned incorporated, the design of windows for guaranteeing adequate lighting levels seems to be an efficient architectonic strategy. In that context, computational simulation results to be an invaluable resource for predicting luminous performance. With the aim to obtain reliable and useful results in daylighting simulation, it´s important, among other, to specify adequate sky types and to use correct metrics. This paper describes the daylight incorporation process into Solar Decathlon 2015´s MIHOUSE prototype and evidences the difficulties founded in the daylight performance evaluation process by using Daylight Factor in the municipality of Cali, Colombia.